Coeliac‐like duodenal pathology in orthotopic liver transplant patients on mycophenolic acid therapy. Issue 4 (21st January 2015) - Cotter, Maura B; AbuShanab, Ahmed; Merriman, Raphael; McCormick, Aiden; Sheahan, Kieran
<x xml:space="preserve">Abstract</x> Aims Diarrhoea following orthotopic liver transplantation (OLT) is a significant clinical problem associated with mycophenolic acid (MPA). The histological injury pattern associated with MPA in the large bowel is well documented in the literature; however, that in the duodenum is less extensively documented. The aim of this study was to investigate the histological spectrum of duodenal injury specifically in symptomatic OLT patients on MPA, and to compare this with the spectrum in patients with coeliac disease and in normal controls. Methods and results We reviewed our pathology database for all duodenal biopsies from patients on the OLT list over a period of 19 years. Medical records, anti‐tissue transglutaminase IgA serology and histology were reviewed. Of the 667 patients who underwent endoscopy, 127 had duodenal biopsies (152 biopsies). Of these, 87.5% were normal. Sixteen showed abnormal histology, and seven (43.8%) of these were on MPA at the time of biopsy. Significant features included coeliac‐like changes (shortened villi and increased intraepithelial lymphocyte counts), and novel findings included increased endocrine cell counts, apoptotic counts and lamina propria eosinophil counts in comparison with normal duodenal biopsies. Conclusions Pathologists should be aware of the features of MPA‐associated duodenal injury, including coeliac‐like changes and increased apoptotic counts. In those with abnormal histology, discontinuation or a reduction in the dose of MPA should be discussed.